Nanopesticides: A Systematic Review of Their Prospects With Special Reference to Tea Pest Management - Deka, Bhabesh; Babu, Azariah; Baruah, Chittaranjan; Barthakur, Manash (Frontiers in Nutrition, 2021)
Background: Tea, the natural beverage is made from tender leaves of the tea plant (Camellia sinensis Kuntze). Being its perennial and monoculture nature of cultivation system; it provides a stable micro-climate for various insect pests, which cause substantial loss of crop. With the escalating cost of insect pest management and increasing concern about the adverse effects of the pesticide residues in the manufactured tea, there is an urgent need to explore other avenues of alternate pest management strategies. Aim: Integrated pest management (IPM) in tea invites multidisciplinary approach owing to high pest diversity in perennial tea plantation system. In this review, we have highlighted on current developments of nanotechnology for crop protection and the prospects of nanoparticles (NPs) in plant protection, emphasizing the control of different major pests of tea plantations. Methods: Literature search was performed using ScienceDirect, Web of Science, Pubmed and Google Scholar search engines with terms – nanotechnology, nanopesticides, tea and insect pest. Article search was concentrated on developments since 1988. Results: We have described the impact of various pests in tea production and innovative approaches on the use of various biosynthesized and syntheric nano pesticides against specific insect pest targets.Simultaneously, we have provided the support on which NPs based technology and their different categories that are currently employed for the management of pests in different agro-ecosystems. Besides the broad categories of active ingredients (AI) of synthetic insecticides, pheromone and natural resource-based molecules having pesticidal activity can also be used using NPs as a carrier as an alternate of traditional pest control agents. Finally, the merits and demerits of incorporating NP-based nano pesticides are also illustrated. Conclusions: Nano pesticides for plant protection is an emerging research field, offers new methods to design active ingredients amid nanoscale dimensions. Nanopesticide based formulations have a potential and bright future for developing more effective and safer pesticide/biopesticides.